Optimalisasi Kinerja UMKM Zona Madina Dompet Dhuafa melalui Pencatatan Keuangan dan Pemasaran Digital Terpadu - Rif'an Ali Hafidz; Oktania Handayani; Safa Aulia Fahmi; Jamilah Jamilah; Novia Tri Wahyuni (Yayasan Literasi Sains Indonesia, 2025)
This community service activity was carried out with the aim of optimizing the performance of Micro, Small, and Medium Enterprises (MSMEs) through the implementation of structured financial recording and the use of integrated digital marketing at the Madina Dompet Dhuafa Zone MSME House. MSMEs are one of the important pillars in the national economy, but many MSME actors still face various challenges, especially in financial management and effective marketing strategies. Lack of financial understanding causes difficulties in monitoring cash flow and measuring business profits. On the other hand, limitations in utilizing digital technology make MSMEs less able to compete in the digitalization era. Through this service program, the team provides simple but applicative financial recording training, as well as digital marketing workshops that include the use of social media, e-commerce, and online promotion strategies. Assistance is carried out intensively so that MSME actors are able to apply the knowledge provided in their daily business activities. The results of the activity show that there is an increase in MSME actors' understanding of the importance of neat financial records, as well as increased skills in utilizing digital platforms to expand marketing networks. With the integration of financial recording and digital marketing, fostered MSMEs at the Madina Dompet Dhuafa Zone MSME House are able to increase efficiency, expand the market, and strengthen competitiveness. This service activity is expected to be a model for sustainable MSME empowerment that can be replicated in other regions as an effort to strengthen the community's economic resilience.